Prevalence of vancomycin-resistant enterococci in hospital and community environment. - Kolár, Milan; Pantůcek, Roman; Vágnerová, Iva; Cekanová, Luboslava; Kesselová, Michaela; Sauer, Pavel; Koukalová, Dagmar; Kolár, Vladislava; Růžiˇková, Milan; Dosar, Jirí (Klinicka mikrobiologie a infekcni lekarstvi, 2005)
The presented study aimed at determining the prevalence of vancomycin-resistant enterococci (VRE) in rectal swabs taken from both patients in the Teaching Hospital in Olomouc (THO), Czech Republic, and subjects from the community setting of the hospital's catchment area. Between July 1, 2002 and July 1, 2003, rectal swabs were taken from the THO patients as well as individuals from the community catchment area to be utilized for isolating and identifying enterococci and their suscetibility to antibiotics. Vancomycin resistance phenotypes were verified by PCR detection of vanA, vanB, vanC1 and vanC2 genes. A molecular biology analysis was performed in VanA Enterococcus faecium strains. To determine the relationship of strains, macrorestriction analysis of the total chromosomal DNA digested with SmaI restriction endonuclease was used. During the observed period, 2,157 rectal swabs from the hospitalized patients and 4,874 rectal swabs from the subjects in community setting were examined. In total, 27 VRE of hospital origin and 13 community-population strains were isolated. The prevalence of VRE in the gastrointestinal tract was 2.3 % in the hospitalized patients and 0.6 % in the community subjects. The prevailing strains were Enterococcus faecium VanA (70.4 %) in the VRE of hospital origin and Enterococcus gallinarum VanC (46.2 %) in the community VRE. Mutual comparison between the hospital and community VRE showed no similarity. In the Czech Republic, VRE were proved both in community and hospital settings. Their prevalence in rectal swabs is low and does not exceed the values reported in other European countries. The author describes the chief characteristics of the most important quinolone antibiotics, including preparations either in their development stage or whose development has been prematurely interrupted because of adverse side-effects. The list includes all preparations that are or were temporarily registered in the Czech Republic.